A Comprehensive Study on Pre-Retirement Planning amongst Botswana Public Officers - Prof. Tshukudu T. Theo; Prof. Ravinder Rena (Researchers World - International Refereed Social Sciences Journal, 2023)
Purpose: The main purpose of this paper was to comprehensively assess the level of knowledge of pre-retirement planning for public officers in the Central District Council of Botswana. Specifically, the paper assessed the pre-retirement planning awareness of public officers by looking at the variables of financial education and retirement investment. In addition, the paper gauged the retirement preparedness of employees nearing retirement by assessing the psychosocial aspects of attitude towards retirement and retirement counselling preparedness. Methodology: the paper adopted a descriptive research design. Using a random sampling method which targeted 100 respondents, a population paper on 62 respondents was conducted, translating to a 62% response rate. The Questionnaires were used for data collection and the results were analysed using description statistics which included frequency tables, pie charts and graphs. Findings revealed that most public officers are aware of retirement planning and those employees falling within retirement age brackets of 45 years old and above, tend to have positive attitudes towards retirement planning. Implications: the paper concluded by observing that majority of public servants does not plan well for their retirement. Therefore, the concept of retirement planning should be introduced in the initial part of public officers’ work life. Originality this paper strategically provides and impetus for the retirement planning and investment among pubic officers in Botswana. The paper assessed pre-retirement planning in the concept of financial retirement planning, as well as the psycho-social aspect of retirement planning.